Photocatalytic Degradation using MWCNTs Modified with Fe(III)-Doped ZnO for Water Treatment - Song, Xiao-Jie; Qin, Zhong-Qiong; Yang, Fan; Fang, Qun-Ling; Hu, Han-Mei; Song, Zhi-Jun (Asian Journal of Chemistry, 2014)
Fe(III) doped ZnO nanoparticles were introduced onto the surface of multi-walled carbon nanotubes (MWCNTs) via in situ chemical precipitation method. The products MWCNTs modified with Fe(III)-doped ZnO nanocomposites (MWCNTs/Fe(III)/ZnO) were characterized by X-ray diffraction, transmission electron microscopy and energy dispersive X-ray spectroscopy. The effects of the ratio of reactants on its dispersion in aqueous solution were analyzed. The nanocomposites with 0.5 mol % Fe(III) showed satisfactory photocatalytic activity in the removal of methyl orange from aqueous solution. Moreover, existence of MWCNTs and doped Fe(III) enhanced the photocatalytic activity of ZnO.